Measuring Biodiversity for Future Forests - Harrington, Kate (Trinity College Dublin. School of Natural Sciences. Discipline of Botany, 2026)
There are a growing number of policies and incentives in Ireland which are aimed at planting new forests to help meet national and international climate and biodiversity goals. While expanding woodland and forest areas is generally viewed positively across political and public spheres, there are important trade-offs to consider, particularly in relation to existing land uses and livelihoods, and the specific ecosystem services that we want these forests to deliver. Since different forests provide different ecosystem services, achieving afforestation goals requires carefully balancing priorities to establish forests that deliver a wide range of benefits for both people and nature, including timber production, climate regulation, and habitat restoration. As biodiversity underpins the benefits forests provide, its measurement has become a shared priority among scientists, policymakers, and investors, providing the evidence needed to track restoration success. In this thesis I use forest data derived from field studies, the Irish National Forest Inventory (NFI), and expert knowledge, to critically examine how we measure forest biodiversity in different contexts. Expanding native woodland cover by planting mixed native species is widely considered beneficial for both biodiversity and climate objectives. However, evidence remains limited on whether these sites, often established on former agricultural land, are on track for long-term success. In newly established woodlands, traditional vegetative indicator metrics may offer insights into whether sites are progressing toward desired habitat types, however such early-stage habitats may also possess ecological value that these metrics fail to capture. Through the study of a chronosequence of woodland sites, I demonstrate the shift from non-woodland to woodland plant communities as sites progress toward canopy closure, with a high proportion of older plots achieving their target woodland habitat. I also find increased colonisation of trees, primarily by hedgerow species, and through incorporating plant trait data and landscape metrics into my analyses, reveal how site and landscape factors affect species assembly, suggesting woodland species may be favoured in low fertility contexts where sessile oak is more frequently planted. This research provides new insights into floral biodiversity changes in planted native woodlands, offering findings relevant to the monitoring and management of such plantations, as well as to broader land-use planning. Increasingly, faunal metrics are being incorporated into a broader suite of measures to demonstrate positive biodiversity change. While most forest monitoring approaches focus on floral or structural metrics, fewer studies have looked at insect responses to developing woodland plantations, and their potential use as a monitoring group. Examining bee and hoverfly communities along a subset of sites associated with the above-referenced chronosequence, I find that the transition toward woodland specialists is less pronounced than for flora, yet compositional shifts are still detectable when beta-diversity metrics are applied. My findings suggest that the bee community may provide a more sensitive and stable metric for assessing woodland development. This research also highlighted the importance of woodland edges as key foraging resources for pollinators. The findings demonstrate how pollinator data can offer multiple insights depending on the metrics applied. These metrics, whether used for ecosystem service assessment or conservation policy, could help set interim targets for tracking afforestation progress. This study emphasises the challenges of monitoring transitional habitats and the importance of selecting appropriate sampling methods, target taxa, and biodiversity metrics. Expanding from a regional to a national scale, I analysed the NFI dataset, using a two-step modelling process, with two aims: first, to investigate the factors influencing floral biodiversity across the Irish forest estate, an area not previously explored using this rich resource, and second, to determine which commonly used proxies for biodiversity best align with direct measures. The findings highlight the structural or categorical metrics that may be of most use in reflecting floral biodiversity, with evidence that the number of tree species, deadwood logs, semi-natural establishment, bryophyte cover, and uneven aged forests are linked to higher overall floral diversity, or that of woodland species. My findings also support the use of floral diversity data from the NFI as a direct compositional biodiversity indicator, encoding both site and landscape influences, that can be derived from the current inventory with no additional survey effort and minimal data processing. I suggest that the identified indirect indicators, direct measurements of floral diversity, or a combination thereof, could inform the selection of metrics for reporting requirements under the Nature Restoration Regulation, devising condition criteria for ecosystem service accounts, or monitoring forest biodiversity in the context of offsetting proposals or sustainable forest management. My study shows how the NFI data can be harnessed to both provide more information on biodiversity across the forest estate, and help identify indicators of forest biodiversity for a wide range of potential uses. Finally, I examined the limitations of NFI data for determining the biodiversity value of future planting scenarios and addressed knowledge gaps by drawing on expert knowledge. Using the Delphi technique, I surveyed a panel of ecologists and foresters, asking them to score the biodiversity value of three potential future planting scenarios across the production forest life cycle. The scores reflected the influence of light availability and stand structure changes associated with canopy closure and thinning. Unexpectedly, the two professional groups were closely aligned in their assessments, with only minor differences. Employing expert elicitation methods alongside available evidence allows us to harness the breadth of existing knowledge, facilitate integration with ecosystem service models, and can meaningfully contribute to quantifying the nature-related impacts of future afforestation policies. This thesis advances our understanding of what constitutes successful native woodland establishment, identifies the components of biodiversity we should be measuring to meaningfully track biodiversity change, and outlines appropriate metrics and monitoring approaches for different conservation and policy contexts.
APPROVED
Keywords: Biodiversity; Forest; Woodland; Nature